The Wide Camp Sea, or Notes on Sontag - Sholem Krishtalka (University of Edinburgh, 2007)
Just as camp under-girds my persona, it contains my project. It provides the universe for my work; it sets the physical laws, determines the essential relationships, and establishes the particular gravity that holds down my ideas. Understand: I don't want to define camp. I'll approach definition, as a by-product of my explications. I make no pretense to tracing limits. If anything, I want to be expansive. I might fail in my attempt at expansiveness, but that's alright; camp has a particular generosity towards failure. Didn't Susan Sontag declare, on camp's behalf, that it consists in "a seriousness that fails"? (285)